The Influence of Depression, Anxiety and Somatization on the Clinical Symptoms and Treatment Response in Patients with Symptoms of Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia - Yang, Yong June; Koh, Jun Sung; Ko, Hyo Jung; Cho, Kang Joon; Kim, Joon Chul; Lee, Soo-Jung; Pae, Chi-Un (Journal of Korean medical science, 2014)
This is the first study to investigate the influence of depression, anxiety and somatization on the treatment response for lower urinary tract symptoms/benign prostatic hyperplasia (LUTS/BPH). The LUTS/BPH patients were evaluated with the Korean versions of the International Prostate Symptom Score (IPSS), the Patient Health Questionnaire-9 (PHQ-9), the 7-item Generalized Anxiety Disorder Scale (GAD-7) and the PHQ-15. The primary endpoint was a responder rate defined by the total score of IPSS (≤ 7) at the end of treatment. The LUTS/BPH severity was significantly higher in patients with depression (whole symptoms P = 0.024; storage sub-symptom P = 0.021) or somatization (P = 0.024) than in those without, while the quality of life (QOL) was significantly higher in patients with anxiety (P = 0.038) than in those without. Anxious patients showed significantly higher proportion of non-response (odds ratio [OR], 3.294, P = 0.022) than those without, while somatic patients had a trend toward having more non-responders (OR, 2.552, P = 0.067). Our exploratory results suggest that depression, anxiety and somatization may have some influences on the clinical manifestation of LUTS/BPH. Further, anxious patients had a lower response to treatment in patients with LUTS/BPH. Despite of limitations, the present study demonstrates that clinicians may need careful evaluation of psychiatric symptoms for proper management of patients with LUTS/BPH.